El ceremonial republicano y los rituales políticos de la Confederación Perú-Boliviana, 1821-1839 - Forsyth, Michael (2023)
This article explores the evolution of Peruvian national rituals and ceremonies, and their relationship with the changing political context from independence to the end of the Restoration War, led by Agustín Gamarra, to understand the lack of political rituals that characterized the Peru-Bolivian Confederation. For this, primary sources such as the newspaper El Peruano, and Guías de forasteros entre 1821 y 1840, as well as official documents of the Peru-Bolivian Confederation and the Colección de leyes, decretos y órdenes publicadas en el Perú desde el año de 1821 hasta el 31 de diciembre de 1859, have been used. This investigation seeks to show that Santa Cruz’s project lacked essential ritual practices to materialize, despite the will of the confederal government to have such practices.